Role of miRNAs in regulation of SA-mediated upregulation of genes involved in folate and methionine metabolism in foxtail millet - Hou, Siyu; Men, Yihan; Zhang, Yijuan; Zhao, Kai; Ma, Guifang; Li, Hongying; Han, Yuanhuai; Sun, Zhaoxia (Frontiers in Plant Science, 2022)
The effect of exogenous salicylic acid (SA) on folate metabolism and the related gene regulatory mechanisms is still unclear. In this study, the panicle of foxtail millet treated with different SA concentrations showed that 6 mM SA doubled the 5-methyltetrahydrofolate content compared to that of the control. An untargeted metabolomic analysis revealed that 275 metabolites were enriched in amino acid metabolic pathways. Significantly, the relative content of methionine (Met) after 6 mM SA treatment was 3.14 times higher than the control. Transcriptome analysis revealed that differentially expressed genes were mainly enriched in the folate and amino acid biosynthesis pathways (including Met, Cys, Pro, Ser et al.). The miRNA−mRNA interactions related to the folate and Met metabolic pathways were analyzed and several likely structural gene targets for miRNAs were identified, miRNA-seq analysis revealed that 33 and 51 miRNAs targeted 11 and 15 genes related to the folate and Met pathways, respectively. Eight key genes in the folate metabolism pathway were likely to be up-regulated by 14 new miRNAs and 20 new miRNAs up-regulated the 9 key genes in the Met metabolism pathway. The 6 miRNA−mRNA interactions related to the folate and Met metabolism pathways were verified by qRT−PCR, and consistent with the prediction. The results showed that DHFR1 gene expression level related to folate synthesis was directly up-regulated by Nov-m0139-3p with 3.8 times, but DHFR2 was down-regulated by Nov-m0731-5p with 0.62 times. The expression level of CYSC1 and APIP related to Met synthesis were up-regulated by Nov-m0461-5p and Nov-m0664-3p with 4.27 and 1.32 times, respectively. Our results suggested that exogenous SA could induce the folate and Met accumulated in the panicle of foxtail millet. The higher expression level of DHFR1, FTHFD, CYSC1 and APIP in the folate and Met metabolism pathway and their regulators, including Nov-m0139-3p, Nov-m0717-5p, Nov-m0461-5p and Nov-m0664-3p, could be responsible for these metabolites accumulation. This study lays the theoretical foundation for elucidating the post-transcription regulatory mechanisms of folate and Met metabolism.